On the Nature and Treatment of Scrupulosity - Deacon, Brett; Nelson, Elizabeth A. (Pragmatic Case Studies in Psychotherapy, 2008)
Obsessive-compulsive disorder (OCD) focused on religious themes, also known as scrupulosity, is a relatively common but poorly understood form of this disorder. It also presents unique challenges to the therapist who must negotiate the procedures of exposure and response prevention while respecting the patient’s religious beliefs and practices. Garcia (2008) describes the successful treatment of Bridget, a 21-year-old woman with scrupulosity, using cognitive-behavioral therapy. Following resolution of her OCD symptoms, a second treatment phase targeted several more interpersonal problems using an integrated cognitive-behavioral and psychodynamic approach. This commentary reviews the nature of religion in OCD, the utility of functional analysis and case formulation, issues in the delivery of cognitive and behavioral techniques in OCD, working with religious compulsions, and the integration of cognitive-behavior therapy (CBT) and psychodynamic approaches in the second phase of Bridget’s treatment.